Digitalization in Pharmaceutical Industry: A Recent Perspectives - Glenn Hole; Anastasia S. Hole; Ian McFalone-Shaw (Innovations in Science and Technology Vol. 5, 2022)
The digitalization of any manufacturing industry is a critical step in the advancement of the manufacturing process. The digitalization process includes increased use of robotics, automation solutions, and computerization, allowing for cost savings, increased efficiency and productivity, and greater adaptability to change. Pharmaceutical Industry (PI) has however been resistant to digitalization, mainly due to fair experience and complexity of the entailed development and manufacture processes. Nevertheless, there is a clear need to digitalize PI as the de- mand in both traditional and new drugs is constantly growing. Contract Development Manufacture Organizations (CDMOs) have a special digitalizing challenge. Digitalization of PI, and CDMO precisely, should be tightly related to the main aspects of Good Manufacture Practice (GMP), and, to succeed in PI digitalizing requires constant focus on GMP. Close collaboration with constantly changing stakeholders is another important factor which should be in focus during digitalization of CDMO. This paper represents an overview over the main aspects of CDMO digitalization and discusses both the opportunities and challenges of the process, focusing on the practical solutions for successive digital implementation.